CLASSROOM LEARNING ENVIRONMENT IN PAKISTAN INSTITUTE OF PROSTHETIC AND ORTHOTIC SCIENCES: STUDENTS’ PERSPECTIVE - Hussain, Sajjad (Journal of Ayub Medical College Abbottabad, 2011)
Background: In 2009 the ISPO team conducted an analysis of the student performance at Pakistan Institute of Prosthetic and Orthotic Sciences (PIPOS) and concluded the situation ’˜unsatisfactory’. This study aims to explore the opinions of the current students regarding the nature of the classroom learning climate at PIPOS. Methods: This survey was carried out in 2010 at PIPOS, Peshawar. The data was collected on a self adapted questionnaire based on a literature review. It was distributed among the 48 students. The data was considered non-parametric categorical, hence contingency table statistics is applied in descriptive format. The statistics were analysed at 95% CI. Results: The replies reveal that the variables tested were imperative and it was appalling that the majority went for second score ’˜Fair’ while fewer were in grade ’˜Good’. Conclusion: PIPOS stands low in the ISPO 2010 report, with a high student failure rate due to issues related to curriculum and teaching methodology. There is a lot to improve relating the students’ level up to the international standards. Keywords: Interpretive study, assessing student perception, classroom learning environment, ideal class room environment